The Dispersion Composition of Polymethylmethacrylate Suspensions and Molecular Weights of Polymers Obtained by Suspension Polymerization in the Presence of Acrylic Copolymers as Surfactants - I. A. Gritskova; O. A. Satskevich; E. S. Klyuzhin; A. I. L’vovskiy; A. V. Andreeva; N. S. Мukha; M. I. Haddaj; S. M. Levachev (Тонкие химические технологии, 2019)
The dispersion composition of polymer suspensions and molecular weights of polymers obtained by suspension polymerization of MMA in the presence of polymer surfactants – methylmethacrylate and methacrylic acid copolymers – were studied. It is shown that a highly dispersed fraction of particles with diameters of 0.02–2.0 µm and a fraction of particles with large diameters (up to 1000 µm) are always present in the polymer suspension. After fractionation of polymer suspensions 3 fractions of particles with different diameters were obtained. For each particle fraction the molecular masses of polymers were determined by viscometry. A significant difference in the values of the molecular masses of polymers obtained as particles of small and large diameters – 105 and 106 Da, respectively – is shown. The presence of a highly dispersed fraction of particles in which a polymer of high molecular weight is formed has a noticeable effect on the average molecular weight of the polymer. In particles of small diameter polymerization takes place according to a mechanism close to the emulsion, due to the fact that the volume of such particles contains a small amount of radicals. The high rate of polymerization leads to the formation of a polymer of high molecular weight, the appearance of a gel effect and a decrease in the termination constant. In most particles, polymerization proceeds by a mechanism close to the solution polymerization, and polymers of low molecular weight are formed. This makes it possible to synthesize polymers of a given molecular weight in drops of certain dispersity.